2021
DOI: 10.1161/strokeaha.120.033149
|View full text |Cite
|
Sign up to set email alerts
|

INSTRuCT

Abstract: Background and Purpose: Very few large scale multicentric stroke clinical trials have been done in India. The Indian Council of Medical Research funded INSTRuCT (Indian Stroke Clinical Trial Network) as a task force project with the objectives to establish a state-of-the-art stroke clinical trial network and to conduct pharmacological and nonpharmacological stroke clinical trials relevant to the nation and globally. The purpose of the article is to enumerate the structure of multicentric stroke net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The trial started in September 2022, and is expected to be completed by August 2025, corresponding to a total duration of 36 months. There are 12 study sites across the country which are part of the Indian Stroke Clinical Trial Network (INSTRuCT) collaborative sites 6. The protocol has been written in accordance with Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The trial started in September 2022, and is expected to be completed by August 2025, corresponding to a total duration of 36 months. There are 12 study sites across the country which are part of the Indian Stroke Clinical Trial Network (INSTRuCT) collaborative sites 6. The protocol has been written in accordance with Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The INSTRuCT Network, CCC comprises of JDP, the Principal Investigator (PI) with Information Technology (IT) personnel, two National Coordinators (SJV and DA), one Statistician and Research Associate (AD). (Pandian et al, 2021). The primary responsibility of the PE will lie with SJV.…”
Section: Sample Recruitment and Study Organisationmentioning
confidence: 99%
“…The main results of the SPRINT India PE will be published by approval from the INSTRuCT Steering Committee with appropriate authorship determined by the steering committee and as per International Committee of Medical Journal Editors (Pandian et al, 2021). The corresponding author would specify the chosen citation, correctly identify all individual authors and list additional group members in the acknowledgements (Pandian et al, 2021).…”
Section: Ethical Approval and Reporting Of Pe Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…With growing uptake of adaptive features (Table 1), it is important to consider the role of professional organisations (e.g., World Stroke Organisation, European Stroke Organisation) and networks (e.g., CanStroke Recovery Trials, Canadian Stroke Consortium, Australasian Stroke Trials Network, NIH StrokeNet 48 , Global Alliance of Independent Networks focused on Stroke trials (GAINS), Indian Stroke Clinical Trial Network (INSTRuCT 49 )), European Stroke Organsiation Trial Alliance (ESOTA 50 )) to prepare current and future generations of clinical trialists to embrace, where appropriate, adaptive trial designs. Clinical trial stakeholders have identified that broadening the acceptance and uptake of adaptive trials will depend on access to training, guidelines, and toolkits to ensure proper use of adaptive trial designs in practice 51 .…”
Section: Introductionmentioning
confidence: 99%